Characterization Of Regenerated Cellulose Films From Oil Palm Empty Fruit Bunch Incorporated With Bifeo3 As A Potential Photocatalyst - Dinesh Weerasooriya, Poonanulkarage Ruwan (2022)
There is an increasing interest in regenerated cellulose (RC) films for advanced applications using natural polymers and renewable materials. Also, photocatalytic degradation is an ecofriendly novel approach to purify waste water. Initially, RC films were isolated via solution casting process using oil palm empty fruit bunch (OPEFB) based microcrystalline cellulose (MCC) and the ionic liquid 1-butyl-3-methylimidazolium chloride ([BMIM]Cl). Effects of MCC on the structures and physicochemical properties of the isolated RC films were determined for 4 wt%, 6.5 wt%, and 9 wt% of MCC at 80 °C. Several analytical methods were employed to evaluate degree of crystallinity, chemical stability, mechanical properties, morphology, opacity, water vapor permeability and thermal stability of the RC films. The results showed that the addition of 6.5 wt% of MCC yielded the greatest tensile strength, 10.2 MPA.